The Inverse Nodal problem for the fractional diffusion equation - Bas, Erdal (Univ Estadual Maringa, Pro-Reitoria Pesquisa Pos-Graduacao, 2015)
In this paper, on a general finite interval, the inverse problem of recovering the potential function for a fractional diffusion equation with new spectral parameter, called the nodal point, is given. Furthermore, using Mittag Leffler function, asymptotic formulas for nodal points and nodal length for a fractional diffusion equation are also found.
Keywords: fractional calculus; fractional diffusion equation; inverse nodal problem; Mittag Leffler function; asymptotic formulas